Training on making handicrafts from natural materials and plastic waste for child activists and educators - Jessica Elfani Bermuli; I. Ismanto; Egilia Lucky; Monica Lamtiur Manullang (Journal of Community Service and Empowerment, 2023)
Ecobrick and ecoprint are one of several solutions that can be used to reduce plastic waste through making crafts resembling stone blocks and synthetic dyes. The aims of the training on handicrafts of natural materials and plastic waste are participant can understand the content and purpose of this webinar, able to provide an evaluation for the entire webinar activity as part of the role of humans who are the crown of God's creation in carrying out cultural mandates, able to increase commitment participants in contributing to share this webinar activity with the public, and also to participate in supporting the SDGs program especially on minimizing the disposal of chemicals and hazardous materials and increasing recycling such as recycling single-use plastics into Ecobricks. Activities are carried out in five stages, observation and problem identification, preparation, work, webinar, and evaluation. The analysis method used is descriptive quantitative. The evaluation results were given to participants after the event and calculated using Ms. Excel. The evaluation is carried out by providing nine questions that will be answered by training participants. The results of the evaluation show that participants become more educated about the use of natural materials and used plastics to be used as handicrafts. The results were 5% neutral answers, 25% answered affirmatively, and 70% answered strongly agreed about the success of the activity.